2021
DOI: 10.3390/biology10070614
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endocrine System in the Regulation of Female Insect Reproduction

Abstract: The proper synthesis and functioning of ecdysteroids and juvenile hormones (JHs) are very important for the regulation of vitellogenesis and oogenesis. However, their role and function contrast among different orders, and even in the same insect order. For example, the JH is the main hormone that regulates vitellogenesis in hemimetabolous insect orders, which include Orthoptera, Blattodea, and Hemiptera, while ecdysteroids regulate the vitellogenesis among the insect orders of Diptera, some Hymenoptera and Lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 98 publications
0
30
0
Order By: Relevance
“…Age-specific expressions of resistance development are also very important, as they provide valuable information regarding the status of insect pests. Furthermore, a proper understanding of the insect endocrine system also helps to better understand the insect reproductive system, which in turn allows the development of new strategies to control insect pest [40]. If an immature stage is more sensitive, then such a stage can be targeted to not only control the insect pests, but also to keep the resistance development under control [21].…”
Section: Discussionmentioning
confidence: 99%
“…Age-specific expressions of resistance development are also very important, as they provide valuable information regarding the status of insect pests. Furthermore, a proper understanding of the insect endocrine system also helps to better understand the insect reproductive system, which in turn allows the development of new strategies to control insect pest [40]. If an immature stage is more sensitive, then such a stage can be targeted to not only control the insect pests, but also to keep the resistance development under control [21].…”
Section: Discussionmentioning
confidence: 99%
“…In lepidopterans, hormone control of reproduction appears to have evolved independently in different lineages. For example, in H. armigera and Manduca sexta , which synthesize Vg in adults, JH plays a significant role in regulating female reproduction, whereas in B. mori , where vitellogenesis proceeds before adult emergence in the absence of JH, 20E is the essential hormone controlling egg development ( Roy et al, 2018 ; Khalid et al, 2021 ). Recent findings in B. mori showed that Kr-h1 was highly expressed in ovaries during the late pupal and adult stages and the expression was induced by 20E ( Zhu Z. et al, 2021 ).…”
Section: Kr-h1 Acts As An Activator In Female Reproductionmentioning
confidence: 99%
“…Parallel studies in diverse insects showed that like ecdysone, the juvenile hormone, known for its role in larval development, also participates in egg development in adult insects. Details of the precise roles of these two key hormones, and the ease of investigating their interactions, vary considerably and are influenced by life history traits such as food source and feeding patterns, longevity, diapause and migration [ 45 ]. This diversity has been particularly well-investigated in several Lepidoptera [ 44 ], while in Diptera, the most detailed studies are based on the yellow fever mosquito Ae.…”
Section: In Vitro Approaches To Insect Biologymentioning
confidence: 99%